Breast density from screening mammography procedure in Malaysia: result of preliminary study - Abdul Hamid , Siti Selina; Jamal , Noriah; Mahamad, Juliana; Samad Cheung, Humairah; Che Mohamed, Siti Kamariah; Muhammed Nordin, Ellyda; Hassan, Radhiana (2013)
Purpose: The primary objective of this study was to determine the breast densitv from screening mammography procedure in Malaysia. The secondary objective was to determine breast density among three major ethnic groups and the effect towards age on breast density among the three major ethnic groups of women in Malaysia. Methods: The study was conducted at two randomly selected mammography centres in Malavsia, namely National Cancer Society and International lslamic University of Malaysia. This was a retrospective study of 1086 women(481 Malays, 478 Chinese and I27 Indian). The Tabar classification (Pattern l-V) was used to evaluate breast density on digital mammograms. The SPSS package was used for statistical analysis. Results: We found that majority of Malaysian women had dense breast of Tabar pattern I and lV. Chinese women had the highest percentage of dense breast. followed bv Indian and Malay. There was no statistically significant difference in breast densitv in the three major ethnic groups. The breast density reduces with age. Conclusion: We found that majority of Malaysian women had dense breast of Tabar pattern I and lV. Chinese women had the highest percentage of dense breast, followed by Indian and Malay. There was no statistically significant difference in breast density in the three major ethnic groups' The breast density reduces with age.